Wanprestasi Dalam Perjanjian Kredit Perbankan Dengan Jaminan Sertifikat Tanah Ditinjau Dari Undang-Undang Nomor 4 Tahun 1996 - Frengky Apolos Baneftar (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
This study aims to examine the legal protection for creditors in the event of default in credit agreements with land certificates according to Law No. 4 of 1996 and to determine the efforts of creditors against debtors who default on credit agreements. The approach used in this research is normative juridical research (doctrinal) and empirical juridical research (non-doctrinal). Data collection techniques are literature studies and field studies in the form of interviews and observations. The results show that the creditors’ legal protection due to the debtor defaults according to Article 10 of Law Number 4 of 1996 is the previous credit agreement, an underhand or an authentic deed, which guarantees the right of creditors to recover their receivables when the debtor defaults. This authentic deed has the advantage that it can be requested for a grosse deed of debt acknowledgment which has executive power and becomes the basis for execution if the debtor is in default. Efforts that can be taken by creditors against debtors who default are amicable settlements, settlements through legal channels or through the assistance of third parties and settlement of bad loans with the assistance of third parties.